Association of Postpartum Smoking Relapse With Breastfeeding and Body Mass Index. Issue 2 (April 2019) - Duman, Mesude; Timur Taşhan, Sermin; Durgun Ozan, Yeter
Abstract: Objective: This study aimed to determine the relationship between smoking relapse and breastfeeding and body mass index in the postpartum period. Methods: This descriptive, cross-sectional study was conducted between November 2016 and November 2017 in the polyclinic for children's health and common illnesses at a university hospital in eastern Turkey. One hundred eleven women who met the inclusion criteria constituted the sample of the study. The data were evaluated using the analyses of percentage, arithmetic mean, standard deviation, independent-samples t test, analysis of variance, and multiple linear regression. Results: In the study, the week of pregnancy period when the women quit smoking was 8.19 ± 5.17, and the week of postpartum smoking relapse was 8.47 ± 11.76. Furthermore, 72.1% of the women stated that they wanted to quit smoking permanently. The study determined that the status of wanting to quit smoking permanently, the status of smoking while breastfeeding, and gained weight during the last gestation are important predictors of postpartum smoking relapse. Originality and Value: Knowledge on the characteristics of the women who started smoking again in the postpartum period is important for helping women who have quitted smoking in pregnancy but who are prone to relapse as a risk group by health care personnel.